COVID-19 and the Neoliberal Resilience of Food Provision in Istanbul: Non-Regulation and Agility in the Fruit and Vegetable Wholesale Markets - Büke, Atakan; Tatarİ, M. Fatih and Doğan, Orkun (The International Journal of Sociology of Agriculture and Food, 2023)
This research examines the impacts of the COVID-19 pandemic on the Istanbul fresh fruit and vegetable provisioning between March and September 2020. In line with global trends, the measures taken within the scope of the pandemic were expected to cause disruptions in various provision channels. Apart from the logistic problems experienced in the first couple of weeks of the pandemic, we observed that there was no severe crisis in the fresh fruit and vegetable provision systems of Istanbul in 2020. Based on our fieldwork conducted between June and September 2020, we attribute this resilience to two key factors: (1) the non-regulation and ineffective control of pandemic measures, allowing actors to operate without major constraints, and (2) the agility of provision actors in adapting to various channels and positions. By exploring these dynamics, we aim to contribute to discussions on neoliberal resilience, emphasizing the importance of reclaiming the concept of resilience without reinforcing the hegemony of the neoliberal agrifood system.